Ti1−xAgx electrodes deposited on polymer based sensors - Marques, S. M. (2014)
Piezoelectric materials are interesting for the development of sensors and actuators for biomedical applications in areas such as smart prosthesis, implantable biosensors and biomechanical signal monitoring, among others. For acquiring or applying the electrical signal from/to the piezoelectric material, suitable electrodes can be produced from Ti based coatings with tailored multifunctional properties: conductivity and antibacterial characteristics through Ag inclusions. This work reports on Ti1−xAgx electrodes with different Ag/Ti atomic ratios deposited by dc and pulsed magnetron sputtering at room temperature on poly(vinylidene fluoride), PVDF. The X-ray diffraction (XRD) results revealed that the deposition conditions preserve the polymer structure and suggested the presence of crystalline Tiβ phase in pure titanium coating and fcc-Ag phase in pure silver coating. According to the results obtained from scanning electron microscopy (SEM) analysis, the coatings are homogeneous and no clusters were found; since β-PVDF is anisotropic, the deposited coatings replicate the underlying substrate surface. Sheet resistivity values show a typical behavior of a binary alloy system, with low resistivity values for coatings of zone 1 (Ti rich) and zone 3 (Ag rich) and a slightly higher resistivity values in zone 2. The piezoelectricity of the different samples show similar values.